2010
DOI: 10.1001/archsurg.2010.108
|View full text |Cite
|
Sign up to set email alerts
|

Are Additional Localization Studies and Referral Indicated for Patients With Primary Hyperparathyroidism Who Have Negative Sestamibi Scan Results?

Abstract: Additional imaging with neck ultrasonography is helpful for selecting minimally invasive parathyroidectomy in most patients with primary hyperparathyroidism who have negative sestamibi scan results. Referral for parathyroidectomy may be considered in patients with negative sestamibi scan results because these results are associated with multigland disease and lower cure rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…It is also important that the requisition form has been properly completed, giving full information not only on the history but also on laboratory findings. The quality of the picture is important too [13][14][15][16].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…It is also important that the requisition form has been properly completed, giving full information not only on the history but also on laboratory findings. The quality of the picture is important too [13][14][15][16].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%
“…Then again, it does reflect the ability to achieve a good surgical success rate in a modest volume setting even in MIBI "negative" patients. The observed surgical success rate in a modest volume institution contradicts the conclusions from others to treat MIBI "negative" patients only in high volume institutions [20]. Furthermore we did not investigate the contemporary use of SPECT or SPECT/CT, however MIBI is a readily available technique and was used in our hospital in the past decade.…”
Section: Discussionmentioning
confidence: 56%
“…This final question relates to the impact on surgical outcome. As mentioned above, the success of surgery consisting of bilateral neck exploration is suboptimal in patients with a negative sestamibi scan (close to 90%) [14,15,28]. Based on the results of 18 F-fluorocholine PET/CT imaging in the series by Quak et al, 18 of 24 patients were able to receive targeted surgery, which is interesting.…”
mentioning
confidence: 99%
“…Some recent studies have shown significant differences in surgical cure rates between patients with a negative sestamibi scan receiving bilateral neck exploration and those with a positive sestamibi scan (e.g. 89% vs. 97%, P = 0.008 [14]; and 90.4% vs. 97.5%, P < 0.001 [15]). It has also been found that patients with a negative sestamibi scan are less likely to be referred to the surgeon [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation